Honeybush tea quality: Effect of water source and evaluation of NIR hyperspectral imaging as a tool to predict quality - Van Schoor, Helene Mijas (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScFoodSc)--Stellenbosch University, 2022.